Assessment of radionuclides and heavy metals distribution and inventories in Kuala Selangor coastal area / Umi Kalsum Abdul Karim - Abdul Karim, Umi Kalsum (2015)
This study was carried out to determine the distribution of radionuclides and selected heavy metals in surface seawater, to determine the sedimentation rate, to determine the distribution and inventories of naturally occurring radioactive material (NORM) and selected heavy in sediment and finally to calculate the radiation hazard index (H ex) and assess level of heavy metal contamination in sediment using geo-accumulation index (Igeo). The study area was divided into four sections which covered 30 kilometers along Kuala Selangor coastal area and estuary and about 2 kilometers into Selangor River. The determination of U and Th in seawater did not showed any significant trend along the coastal area. Besides, no significant relationship were observed between U and Th concentrations and value of salinity in the samples which may due to low salinity oceanic environments that occurred in the estuaries and makes the behavior seems more variable. Besides, the concentrations of heavy metals (Pb, Cd and Ni) were varied between stations and most of the stations fairly contaminated with Pb. In addition, the mean concentrations of heavy metals in surface water in Section 4 are well below the Malaysian Drinking Water Quality Standard. The sedimentation rate value in the study area were closer with other study which is in the ranged of 0.1547 - 0.3397 cm/year and most of the stations in Section 3 showed high sedimentation rate than other sections which may due to an increase in land clearing activities at the catchment area of Sungai Selangor. The distribution of NORM in most of the cores showed that it was in the mixing layer based on the inconsistent variation of the activity concentration of NORM. Furthermore, total inventories of 226Ra, 228Ra and 40K in the sediment core were not differ very much between the stations. However, station SS3 in Section 4 displayed the highest inventories of 226Ra and 228Ra which may suggested that the input of Ra from the past mining activities was significant in the area. By comparing the heavy metal concentration in sediment with the average shale standard and New York Sediment quality Guideline, most of the stations in Section 3 and Section 4 exceed the standard. This may suggest that the anthropogenic activities and complex processes that occur in the estuary have elevated the concentration of heavy metals in the area. Moreover, the increased of Pb and Cd in bottom sediment may due to land use changes in Kuala Selangor in 19th century such as mining activities, land clearing for development, industrial and aquaculture and agriculture activities. Besides that, most of the stations in Section 3 showed high inventories of Pb, Cd and Ni which may due to active industrial, agricultural and aquacultural activities along the Sungai Selangor and Kuala Selangor coastal area and also high sedimentation rate in the area. The external hazard index (Hex) in all location is lower than the permissible value which is 1 and the Igeo values have indicated that the quality of sediment in Section 1 and Section 2 was not polluted as compared to Section 3 and Section 4.